Unity and variety in the Jesuit mission of the 16th-century: from Japan to the borders of the Hispanic Monarchy - Gómez Díez, Francisco Javier (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
This article seeks to portray, through a comparative analysis, the missionary method of the Society of Jesus, considering the charisma, the centralized structure of the Institute and all the concrete criteria which has been developed since the times of Ignatius. While the Japanese method is based on the importance of rationality, the need to go more in depth in the acculturation process and in the rapid development of a native clergy, the American world is marked by two experiences: the establishment of the European political sovereignty that protects and guarantees the missionary activity, and the fall of the native, pre-hispanic cosmogony, which leads the indigenous to seek in the mission a way of protection against the uprooting of the new social elites. Perhaps it is because of this reason that the acculturation is of lesser depth in America.
Keywords: Society of Jesus; Latin-America; acculturation; missions; missionary method